Peer Effects and the Gender Gap in Corporate Leadership: Evidence from MBA Students - Menaka Hampole; Francesca Truffa; Ashley Wong (The Quarterly Journal of Economics, 2026)
Abstract Women continue to be underrepresented in corporate leadership positions. This article studies the role of social connections in women’s career advancement. We investigate whether access to a larger share of female peers in business school affects the gender gap in senior managerial positions. Merging administrative data from a top 10 U.S. business school with public LinkedIn profiles, we first document that female MBAs are 24% less likely than male MBAs to enter senior management within 15 years of graduation. Next we use the exogenous assignment of students into sections to show that a larger proportion of female MBA section peers increases the likelihood of entering senior management for women but not for men. This effect is driven by female-friendly firms, such as those with more generous maternity leave policies and greater work-schedule flexibility. A larger proportion of female MBA peers induces women to transition to these firms where they attain senior management roles. A survey of female MBA alumnae reveals three key mechanisms: (i) information sharing, especially related to gender-specific advice, (ii) higher ambitions and self-confidence, and (iii) increasing support from male MBA peers. These findings highlight the role of social connections in reducing the gender gap in senior management positions.